The Way Forward on Counter-Terrorism: Global Perspectives - Schmid, Alex P. (Strathmore Law Journal, 2016)
There have been thousands of public conferences and closed-door meetings on terrorism and counter-terrorism since 11 September 2001. They usually end up with recommendations and then everybody goes home after the group photo has been taken. This article will deal with the following questions: what happened to all these recommendations? Who has acted upon them and actually implemented them? Who has evaluated them? Were they any good? Specifically, it will analyze five critical issues: (i) the definition problem; (ii) the communication problem; (iii) the political problem; (iv) the religious problem; (v) the radicalization problem. Finally, it will be provided twelve rules for preventing and combating terrorism.